EIGHTEEN SEA CUCUMBER SPECIES FISHED IN KARIMUNJAWA ISLANDS, JAVA SEA - Purwati, Pradina; Hartati, Retno; Widianingsih, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
Indonesia has been supplying the highest diversity of dried sea cucumbers (trepang) to world markets for decades even though species validation on the trepang from any producing areas throughout the country is still needed. Karimunjawa (Islands off north coast of Java) is one of trepang habitats. Several visits from May to November 2009 had been made to collect trepang from the fishers and collectors in that area. Eighteen aspidochirote species were identified, more varied than those reported in 1988 and 1992 although 7 species have no longer been found. Three species among those: Actinopyga banwarthi, Bohadschia subrubra, and Holothuria fuscocinerea have never been reported in Indonesia before, neither on the list of commercial sea cucumbers in Asia nor world trade provided by Choo (2008) and Toral-Grande (2007). These species composition shifts may indicate a threat to species diversity, starting with excessive removal of natural stock. Up to now, 28 species of trepang have been recognized from Karimunjawa waters.